2020
DOI: 10.1007/s40544-020-0427-7
|View full text |Cite
|
Sign up to set email alerts
|

An efficient three-dimensional foil structure model for bump-type gas foil bearings considering friction

Abstract: This paper presents an efficient three-dimensional (3D) structural model for bump-type gas foil bearings (GFBs) developed by considering friction. The foil structures are modeled with a 3D shell finite element model. Using the bump foil mechanical characteristics, the Guyan reduction and component mode synthesis methods are adopted to improve computational efficiency while guaranteeing accurate static responses. A contact model that includes friction and separation behaviors is presented to model the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Baum et al [96] found that the suggested model is very computationally productive in respect of accuracy and time by using FEM and Galerkin's approach to determine pressure distribution, load-displacement curves, solution accuracy, and simulation time. The 3D deformation simulations of top or bump foil, bearing sleeve, contact between the bump and top foil, FEM approach, and misalignment for discretization have been studied by Yongpeng et al [97] and Zhao and Xiao [98]. They discovered that at the diverging area of the film, the top foil is momentarily disconnected from the assisting bump foil.…”
Section: Theoretical Research On Patbmentioning
confidence: 99%
“…Baum et al [96] found that the suggested model is very computationally productive in respect of accuracy and time by using FEM and Galerkin's approach to determine pressure distribution, load-displacement curves, solution accuracy, and simulation time. The 3D deformation simulations of top or bump foil, bearing sleeve, contact between the bump and top foil, FEM approach, and misalignment for discretization have been studied by Yongpeng et al [97] and Zhao and Xiao [98]. They discovered that at the diverging area of the film, the top foil is momentarily disconnected from the assisting bump foil.…”
Section: Theoretical Research On Patbmentioning
confidence: 99%
“…It is a Winkler foundation model that assumes that the foil deflections are only dependent on the local air pressure. Furthermore, according to the authors of [28,29], the foil is assumed to deform uniformly in the axial direction, which has been shown to be a reasonable assumption. The governing equation of the SEFM with uniform deformation in the axial direction is written as follows:…”
Section: Foil Structurementioning
confidence: 99%
“…After the contact boundary detection, the contact forces between the possible contact patch pairs are calculated sequentially. The algorithm of slave points to master patches 34,44 is used to evaluate the contact forces, as shown in Figure 5C. The contact forces are then converted to equivalent nodal loads for obtaining ILCs.…”
Section: Contact Force Calculationmentioning
confidence: 99%